Analysis on the formation of a FRC by flux measurements and MHD simulations - Kayama, Milton Eiji [UNESP]; Nascimento, Luiz Carlos do; Mota, Rogério Pinto [UNESP]; Kostov, Konstantin Georgiev [UNESP]; Honda, Roberto Yzumi [UNESP]; Algatti, Mauricio Antonio [UNESP] (Iop Publishing Ltd, 2015)
The evolution of the separatrix and excluded flux radius was investigated in a mirror-less theta pinch with external magnetic and loop probes and by numerical simulation. In the numerical hybrid code the anomalous effect was taken as evolution of lower hybrid drift instability. At mid-plane of the coil the experimental and theoretical values of lift-off time, implosion time and equilibrium plasma radius were very close. The implosion time is 5 +/- 1 cm/mu s and the separatrix radius at mid-plane is around one half of the discharge tube radius. Within the experimental uncertainty the excluded flux radius has the same value along the coil, suggesting an elongated configuration with closed magnetic field lines.
Keywords: Excluded flux radius; Separatrix radius; FRC